The Politics of Anti-Gender Campaigns: An Analysis of Congressional Debates In Peru Regarding the Educational Curriculum Reform - Arellano Salazar, Andrea (Université d'Ottawa / University of Ottawa, 2022)
Through the lens of analyses of populist mobilizations informed by political sociology, this study offers a new perspective on tactics used by anti-gender campaigns. Specifically examining the Education Curriculum and the Enfoque de Igualdad de Género [Gender Equality Approach] in congressional debates in Peru in 2018 and 2019, this study uses a qualitative content analysis to identify central themes. The themes reveal tactics that sabotage feminist gains in educational reforms, spearheaded by Christian political actors. The argument is thus that Christian political actors use tactics such as coopting feminist concepts such as “gender” and re-framing it as “gender ideology”. This is an example of using “emotional epistemic loops” of information to achieve political goals, in this case advancing patriarchal Christian values and undermining feminist and gender equality gains.
Keywords: Peru; Populist mobilization; Populism; Gender equality; Gender ideology; Christian politics; Feminism; Catholic Church; Evangelical Church; Anti-gender campaigns